Implementation of Public Sector Accounting to Enhance Performance Accountability and Prevent Fraud: A Case Study at Minasa Upa Community Health Center - Syah, Sri Rahayu; Halmi, Halmi; Asikin, Nurul (Manajemen Multitalenta Indonesia, 2025)
This study analyzes the implementation of public sector accounting in enhancing performance accountability and its role in preventing fraud at Minasa Upa Community Health Center, one of the 12 health centers in Makassar City with BLUD (Regional Public Service Agency) status. The findings indicate that accrual-based financial statements including the Budget Realization Report, Balance Sheet, Operational Report, Cash Flow Statement, Statement of Changes in Equity, and Notes to Financial Statements have been prepared in accordance with applicable standards. This practice strengthens transparency and accountability, as emphasized in Accountability Theory, which asserts that public entities are obligated to account for the management of resources to both society and higher authorities. In terms of fraud prevention, Minasa Upa Health Center implements Government Regulation No. 60/2008 on Internal Control Systems (SPIP) and supports Presidential Regulation No. 54/2018 on the National Strategy for Corruption Prevention. Internal supervision mechanisms, periodic audits, and segregation of financial functions have proven effective in reducing fraud risks, in line with Fraud Triangle Theory, which highlights the roles of pressure, opportunity, and rationalization. Practical Implications: The findings underline the importance of accrual-based accounting as a foundation for strategic decision-making and the strengthening of SPIP through internal audits, tiered supervision, and staff integrity. Academic Implications: This study enriches the literature on public sector accounting and governance by emphasizing the role of accounting standards, accountability theory, and internal control systems in enhancing performance accountability and preventing fraud in Indonesia’s public healthcare sector